Beanspruchungserfassung für die Validierung von FE-Modellen zur Auslegung von Massivumformwerkzeugen - Noneder, Johannes (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
Validating FE-models for tool design of highly loadable tools for forming of very strain hardening materials is challenging. This thesis presents a methodology for enhancing validation of FE-models to achieve better tool load prediction of the FE-models. This is fundamental for designing of highly loadable tools for cold forging of high nitrogen steels. Using these materials enables the production of high strength components without the need of quenching and temperin